2015
DOI: 10.3389/fendo.2015.00153
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptors in the Pathophysiology of Vascular Inflammation and Atherosclerosis

Abstract: Atherosclerosis is a chronic inflammatory disease of the vasculature that causes significant morbidity and mortality from myocardial infarction, stroke, and peripheral vascular disease. Landmark clinical trials revealed that mineralocorticoid receptor (MR) antagonists improve outcomes in cardiovascular patients. Conversely, enhanced MR activation by the hormone aldosterone is associated with increased risk of MI, stroke, and cardiovascular death. This review summarizes recent advances in our understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Perhaps more importantly, the ALDO-induced increase in plaque lipid and inflammatory cell content was also prevented in mice lacking ICAM-1. This has important clinical implications since a plaque phenotype with increased lipids and inflammatory cells is known to contribute to susceptibility to rupture, the cause of most MIs and strokes [16]. This mechanism may therefore explain the increased risk of MI and stroke in patients with elevated ALDO levels [2,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps more importantly, the ALDO-induced increase in plaque lipid and inflammatory cell content was also prevented in mice lacking ICAM-1. This has important clinical implications since a plaque phenotype with increased lipids and inflammatory cells is known to contribute to susceptibility to rupture, the cause of most MIs and strokes [16]. This mechanism may therefore explain the increased risk of MI and stroke in patients with elevated ALDO levels [2,4].…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular leukocytes then take up lipids and form the core of the atherosclerotic plaque. Plaques with increased inflammatory cell infiltrate and lipid content are prone to rupture and thrombosis, and this vulnerable plaque phenotype is the cause of most MIs and strokes [16]. Thus, understanding mechanisms driving plaque progression and inflammation and the role of ALDO/MR, may explain the clinical observations linking ALDO to cardiovascular ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that these antagonists inhibit atherosclerosis, whereas aldosterone, an endogenous agonist of MR, promotes atherosclerosis (8,12). Utilizing a myeloid MR knock-out (MRKO) mouse model, we and others have previously demonstrated that MR regulates macrophage polarization and inflammation and that macrophage MR is important in controlling cardiac and vascular remodeling (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…MR is a hormone-activated transcription factor and most of its long term effects, including renal regulation of blood pressure, are mediated by its genomic actions to regulate gene transcription. Chronic MR antagonism modulates expression of genes that can offset or reverse the initial impairment in endothelium-dependent dilation including activation of anti-oxidant and anti-inflammatory pathways in the endothelium (Reviewed in (Moss and Jaffe 2015)).…”
Section: Discussionmentioning
confidence: 99%